FUTURO PASADO. LA EVOLUCIÓN DEL CONCEPTO “POESÍA” EN OCTAVIO PAZ - CALDERÓN FARFÁN, Alí (Studia Universitatis Babeș-Bolyai Philologia, 2021)
Future Past. The Evolution of the Concept of Poetry in Octavio Paz. Octavio Paz (1914) is a poet writing in Spanish whose aesthetic ideas have built a vision of relevant poetry for at least three traditions: poetry in French, English and, of course, Spanish. This study will analyze, from the metalinguistic perspective proposed by Reinhart Koselleck, how the concept of “poetry” evolved in the thought of the Mexican Nobel Prize winner. Framed by his tradition, by his space of experience, Octavio Paz wrote works that have been instrumental in understanding and valuing poetry in the twentieth century. From “Poesía de soledad y poesía de communion” (1943) to La otra voz, Poesía y fin de siglo (1990), Paz synthesized the aesthetic ideas of his time in El arco y la lira (1956), rethought the lyrical exercise in “Los signos de rotación” (1956), modified his poetic in the prologue to Poesía en movimiento and made his position explicit in Los hijos del limo and his thoughts on Lévi-Strauss and Marcel Duchamp. By focusing on these texts, as well as on a corpus of conferences, interviews, correspondence and even poetry recitals, this study explores the evolution of poetic thought and the horizon of expectations that the work of the last Spanish-speaking poet who received the Nobel Prize opens for us. REZUMAT. Viitorul trecut. Evoluția conceptului de poezie la Octavio Paz. Octavio Paz (1914) este, cel mai probabil, poetul din lumea hispanică ale cărui idei estetice au construit o viziune a poeziei relevantă pentru cel puțin trei tradiții: poezia în limba franceză, în engleză, și, desigur, cea în spaniolă. Pentru acest articol ne interesează, pornind de la metalimbajul propus de Reinhart Koselleck, reflecția în jurul evoluției conceptului de “poezie” în gândirea Premiului Nobel mexican. Încadrat în tradiția sa, adică, de spațiul său de experiență, Octavio Paz a scris texte care au stat la baza înțelegerii și aprecierii poeziei secolului XX. De la “Poesía de soledad y poesía de comunión” (1943) la La otra voz. Poesía y fin de siglo (1990), Paz a sintetizat ideile estetice ale vremii sale în El arco y la lira (1956), a regândit exercițiul liric în “Los signos en rotación” (1965), și-a modificat poetica în prologul la Poesía en movimiento și și-a explicat postura în Los hijos del limo și reflecțiile sale în jurului lui Lévi-Strauss y Marcel Duchamp. Prin aceste texte, precum și cu un corpus de conferințe, interviuri, corespondență și chiar recitaluri, articolul face presupuneri în jurul evoluției gândirii poetice și a orizontului de așteptare, pe care le deschide pentru vremea noastră opera ultimului poet spaniol care a primit Premiul Nobel. Cuvinte-cheie: Octavio Paz, stil, poetică, timp post-utopic, semantica conceptelor